Norman Fairclough’s Views on Language and Globalization - Jora, Man Bahadur (DMC Research Journal, 2018)
This article is based on Fairclough’s views on language and globalization. There are eight subtopics in it. In subtopic 1, there is given a short introduction about the author. In subtopic 2, globalization is discussed in general. In subtopic 3, views on discourse as a facet of globalization in the academic literature are summarized dealing with an approach based upon a version of critical discourse analysis and cultural political economy. In subtopic 4, different strategies of globalization (and regionalization) emanating from governmental and non-governmental agencies, and the different discourses which constitute elements of these strategies are discussed. In subtopic 5, the idea of re-scaling is discussed. Moreover, the national scale in its relation to the global scale and the scale of international regions is presented. In subtopic 6, the media and mediation are dealt for discussion. In subtopic 7, people’s ordinary experience of globalization, and its implications for and effects upon their lives is discussed. Finally, subtopic 8 has focused war and terrorism. This article has emphasized some concepts related to globalization such as modernization, democracy, markets, free trade, flexibility, liberalization, security, terrorism, cosmopolitanism and so forth.